Cumulative exposure to tacrolimus and incidence of cancer after liver transplantation. Issue 6 (31st March 2022) - Rodríguez‐Perálvarez, Manuel; Colmenero, Jordi; González, Antonio; Gastaca, Mikel; Curell, Anna; Caballero‐Marcos, Aránzazu; Sánchez‐Martínez, Ana; Di Maira, Tommaso; Herrero, José Ignacio; Almohalla, Carolina; Lorente, Sara; Cuadrado‐Lavín, Antonio; et al.
Abstract : Cancer is the leading cause of death after liver transplantation (LT). This multicenter case–control nested study aimed to evaluate the effect of maintenance immunosuppression on post‐LT malignancy. The eligible cohort included 2495 LT patients who received tacrolimus‐based immunosuppression. After 13 922 person/years follow‐up, 425 patients (19.7%) developed malignancy (cases) and were matched with 425 controls by propensity score based on age, gender, smoking habit, etiology of liver disease, and hepatocellular carcinoma (HCC) before LT. The independent predictors of post‐LT malignancy were older age (HR = 1.06 [95% CI 1.05–1.07]; p < .001), male sex (HR = 1.50 [95% CI 1.14–1.99]), smoking habit (HR = 1.96 [95% CI 1.42–2.66]), and alcoholic liver disease (HR = 1.53 [95% CI 1.19–1.97]). In selected cases and controls ( n = 850), the immunosuppression protocol was similar ( p = .51). An increased cumulative exposure to tacrolimus (CET), calculated by the area under curve of trough concentrations, was the only immunosuppression‐related predictor of post‐LT malignancy after controlling for clinical features and baseline HCC (CET at 3 months p = .001 and CET at 12 months p = .004). This effect was consistent for de novo malignancy (after excluding HCC recurrence) and for internal neoplasms (after excluding non‐melanoma skin cancer). Therefore, tacrolimus minimization, as monitored by CET, is the key to modulate immunosuppression in order to prevent cancer after LT. Abstract : This case‐control nested study including 2, 495 liver transplant patients demonstrates that cumulative exposure to tacrolimus within the first posttransplant year is an independent risk factor of posttransplant malignancy, thus offering an opportunity for refined dose‐adjustments of this drug in clinical practice.